Analysis of steel bars corrosion as a function of the environment pH - Macioski, G.; de Souza, D. J.; Capraro Brandão, A. P.; de Medeiros, M. H. F. (Revista ALCONPAT, 2016)
The aim of this study is to analyze how the steel type, the environment pH and surface protection of steel bars are able to change the electrochemical properties of this metal. Therefore, it was applied the linear polarization technique to steel bars to assess the corrosion of the samples. The study evaluated the CA-50, CA-60 and CP-175-RB steels bar, with and without surface protection. Studies like this are essential for the improvement of reading techniques, especially for the understanding of the results obtained in repairs already made. From the results, it was possible to observe how the three variables influenced the results of the current density and corrosion rate. Keywords: corrosion rate; durability; pH; linear polarization.